The effects of anisotropy and microcracks on the fracture toughness (KIC) of freshwater ice - Timco, G. W.; Frederking, R. M. W. (1986)
A series of tests have been performed to measure the plane strain critical stress intensity factor (KIC) for columnar freshwater ice as a function of loading rate and loading direction. The results indicate that KIC decreases with increasing loading rate and grain size, and that for comparable conditions, KIC is higher for crack propagation extending along the plane of the ice cover as opposed to crack propagation through the thickness of an ice cover. A separate series of tests indicated that increasing microcrack density resulted in a decrease in the apparent fracture toughness of ice. Les auteurs ont effectué une série d'essais en vue de mesurer le facteur critique d'intensité de contrainte (KIC) en déformation plane de la glace d'eau douce à grains prismatiques, en fonction du taux et de la direction de chargement. Les résultats révèlent que le facteur KIC diminue avec l'accroissement du taux de chargement et de la dimension des grains et que, dans des conditions semblables, KIC est plus élevé dans le cas de la propagation des fissures le long du plan d'une couverture de glace qu' à travers l'épaisseur de la couverture. Une série distincte d'essais a indiqué que l'accroissement de la densité des microfissures donnait lieu à une diminution de la résistance apparente de la glace à la rupture. Peer reviewed: Yes NRC publication: Yes